Self-medication practice and associated factors among adults in Wolaita Soddo town, Southern Ethiopia - Mathewos, Tamirat; Daka, Kassa; Bitew, Shimelis; Daka, Deresse (International Journal of Infection Control, 2021)
Background: Self-medication is the selection and use of medicines by individuals to treat their self-recognized illnesses or symptoms. Self-medication can decrease costs and enable health professionals to concentrate on more serious health problems. Aim: To assess self-medication practice and associated factors among adults in Wolaita Soddo town, Southern Ethiopia, 2017. Methods: An institution-based cross-sectional study was conducted from September 30 to October 30, 2017. A multi-stage sampling technique of drug retail outlets in Wolaita Soddo town was employed to identify 623 individuals that came to buy drugs in the past three months. Data was collected using a structured questionnaire. Results: About 33.7% of the respondents had practiced self-medication in the past 3 months. Multivariate analysis revealed that female sex (adjusted odds ratio (AOR) = 2.22, 95% confidence interval (CI): 1.47–3.36), low income (AOR = 3.95, 95% CI: 2.32–6.73) and higher educational level (AOR = 5.79, 95% CI: 2.47–13.58) were the independent factors significantly affecting the practice of self-medication with drugs. Headache/fever (32.4%), respiratory tract infections (31.4%) and gastrointestinal diseases (16.2%) were the most frequently reported illnesses or symptoms of illnesses that prompted self-medication of study participants. Conclusion: Health education campaigns, strict legislations on dispensing drugs from private pharmacies, and improving accessibility and affordability of health care are among the important interventions required to change people’s health-seeking behavior and prevent the potential risks of self-medication.